Endovideoscopic urethra-sparing simple prostatectomy via an extraperitoneal approach as treatment of benign prostatic hyperplasia - Stanislav N. Volkov; Vitaliy I. Tereshchenko; Vladimir S. Stepanchenko; Robert K. Mikheev; Olga R. Grigoryan; Elena N. Andreeva; Konstantin B. Kolontarev (Consilium Medicum, 2023)
Aim. To evaluate the efficacy of endovideoscopic urethra-sparing simple prostatectomy via an extraperitoneal approach (EUSP) for patients with benign prostatic hyperplasia.